Structural trends in ten-vertex endohedral clusters, M@E(10) and the synthesis of a new member of the family, [Fe@Sn10]3-. - Krämer, T; Duckworth, J; Ingram, MD; Zhou, B; McGrady, J; Goicoechea, J (2013)
The synthesis of a new endohedral ten-vertex Zintl ion cluster, [Fe@Sn10](3-), isoelectronic with [Fe@Ge10](3-), is reported. In an attempt to place this new cluster within the context of the known structural chemistry of the M@E10 family (M = transition metal, E = main group element), we have carried out a detailed electronic structure analysis of the different structural types: viz bicapped square antiprismatic ([Ni@Pb10](2-), [Zn@In10](8-)), tetra-capped trigonal prismatic ([Ni@In10](10-)) and the remarkable pentagonal prismatic [Fe@Ge10](3-) and [Co@Ge10](3-). We establish that the structural trends can be interpreted in terms of a continuum of effective electron counts at the E10 cage, ranging from electron deficient (<4n + 2) in [Ni@In10](10-) to highly electron rich (>4n + 2) in [Fe@Ge10](3-). The effective electron count differs from the total valence electron count in that it factors in the increasingly active role of the metal d electrons towards the left of the transition series. The preference for a pentagonal prismatic geometry in [Fe@Ge10](3-) emerges as a natural consequence of backbonding to the cage from four orthogonal 3d orbitals of the low-valent metal ion. Our calculations suggest that the new [Fe@Sn10](3-) cluster should also exhibit structural consequences of backbonding from the metal to the cage, albeit to a less extreme degree than in its Ge analogue. The global minimum lies on a very flat surface connecting D4d, C2v and C3v-symmetric minima, suggesting a very plastic structure that may be easily deformed by the surrounding crystal environment. If so, then this provides a new and quite distinct structural type for the M@E10 family.